About the “Heat Shock” Phenomenon - Gareyev, А. А. (European Journal of Applied Sciences, 2022)
At present, depletion and diminished performance of oil formations take place. Operation of low production wells is carried out using ESP units at the rate of max. 35 m3/per day under low suction pressure of centrifugal pumps. The drop of the centrifugal pump suction pressure below the saturation pressure leads to liberation of free gas in the pumped mixture. Operation of a centrifugal pump during pumping of gas-cut mixtures results in reduction of the ESP unit efficiency. The loss of the pump efficiency leads to the fact that the substantial part of energy is consumed on heating and temperature rise of the centrifugal pump. Operation of a centrifugal pump at elevated temperatures results in frequent faults of the ESP units and in salt deposition. In some cases, faults of the ESP units may occur out of the blue due to the uncontrolled heat release and temperature rise. Let us call a sudden uncontrolled heating of a centrifugal pump a “heat shock”. The pump failure as a result of a heat shock is normally classified as the “wrongdoing of the oil producing organization personnel”. This article addresses the possibility of detection and elimination of the “heat shock” moment - a sudden ESP failure. Solution of this problem will be useful for design engineering of the pump automatic control.